Basic laboratory procedures in clinical bacteriology - Vandepitte, Jozef (WHO, 2003)
This manual is a practical guide, for use by laboratory workers in health centres and district hospitals, to the procedures to be followed in obtaining specimens, isolating and identifying bacteria, and assessing their resistance to antibiotics. It covers bacteriological investigation of blood, cerebrospinal fluid, urine, stool, sputum, pharyngeal and genital specimens, and purulent exudates. Particular attention is given to the need for quality control of all laboratory procedures. A list of media and reagents needed for the isolation and identification of the most common bacterial pathogens is included, together with an indication of their relative importance for the intermediary laboratory. This list is intended for adaptation to local circumstances. This second edition has been updated in many areas, including a greatly enhanced section on stool specimens and a new section on serological tests.
Keywords: manuály jako téma; chemie, klinická chemie; Clinical Laboratory Techniques; klinické laboratorní techniky; Culture Media; bakteriologické techniky; bakteriologie; Manuals as Topic; Bacteriology; kultivační média; Bacteriological Techniques